Psychiatric Symptom Profiles Predict Functional Impairment - Tanner, Joachim; Zeffiro, Thomas; Wyss, Daniela; Perron, Noelle; Rufer, Michel; Mueller-Pfeiffer, Christoph (Frontiers in Psychiatry, 2019)
Objective: Mental illness often interferes with daily functioning and individual client characteristics may predict risk of future disability. Understanding the linkage between psychiatric symptoms and impaired functioning is critical for rehabilitation planning and legal assessments. Here, we investigated the stability of functional impairment over 18 months and their association with psychiatric symptoms. Moreover, we developed a clinical self-report measure that allows estimation of levels of functional impairment over 18 months. Methods: Consecutively treated outpatients and daycare patients (N = 155) from several psychiatric units in Switzerland completed the Dissociative Experiences Scale, Somatoform Dissociation Questionnaire, Multidimensional Inventory for Dissociation, Beck Depression Inventory, Brief Symptom Inventory, and WHO Disability Assessment Schedule at baseline, 6, 12, and 18 month follow-up examinations. The association between symptoms and course of functional impairment was investigated using longitudinal linear mixed models. Penalized regression was used to identify questionnaire items that best predicted functional impairment. Results: We found high stability in the extent of functional impairment across 18 months. Fear of negative evaluation, fatigue, concentration problems, negative alterations in mood, and dissociative symptoms showed the strongest association with the course of functional impairment. The empirically derived scale for the prediction of functional impairment explained between 0.62 and 0.77 of the variance in disability across various life domains. Conclusion: Given the capability for somatic and mental symptoms associated with social anxiety, depression, and dissociation to predict future disability, these symptoms have strong potential for guiding rehabilitation planning and prognostic evaluation in insurance medicine. The Functional Impairment Prediction Scale may serve as a valuable, empirical-based extension in legal assessments of working capacity.